Public health implications of Bovine Cysticercosis from Cattle slaughtered at Dilla Municipal abattoir, Southern Ethiopia - Fikadu Tesfaye; Jemere Bekele; Mesele Abera; Nebyou Moje Hawas (East African Journal of Biophysical and Computational Sciences)
A cross-sectional study was conducted from November 2013 to June 2014 to estimate the prevalence of Cysticercosis from abattoir survey and Taeniasis within the society found in and surrounding Dilla town. Active abattoir survey and questionnaire survey were performed to accomplish the study. Of the total of 400 inspected cattle carcasses, 17 had a varying number of C. bovis giving an overall prevalence of 4.25% (17/400). Anatomical distribution of the cyst showed that highest proportions of C. bovis cyst were observed in shoulder muscle and tongue (29.41%), followed by, masseter muscle (23.53%), heart (11.76%) and liver (5.88%). Of the total 69 interviewed respondents, 57.79% (40/69) had contracted T. saginata infection. The majority of the respondent had an experience of raw meat consumption (65.2%; 45/69) as a result of traditional and cultural practice. Of those raw meat consumers, 62.2% (28/45) were experienced taeniasis. However, no significant association was observed between raw meat consumption and teanisis (P< 0,05). The findings of this study including the prevalence of C. bovis and questionnaire survey of taeniasis prevalence indicated the importance of Cysticercosis and Taeniasis in public health aspects. Therefore, due attention should be given to the public awareness and strict routine meat inspection in order to safe guard the public health.